Evaluate The Effect of Coenzyme Q10 on The Prevention of Doxorubicin-Induced Acute Cardiotoxicity in Rats. - AL-Shimaysawee, Ola Sadeq; Fadhil Abd aljabbar Rizij; Rafid Mohammed Ali Hassan wasfi (Journal of Contemporary Medical Sciences, 2024)
Objective: This study will evaluate the potential protective effects of coenzyme Q10 on DOX-induced cardiotoxicity in female rats, manifested by changes in biochemical parameters in tissue and serum samples histopathological differences, and compare their changes. Methods:24 female rats were divided into three groups based on weight. The first group received saline, the second group received a cumulative dose of 15 mg/kg of DOX via IP injection, and the third group was pre-treated with CoQ10 before receiving DOX. The data were analysed using a one-way ANOVA test with a Bonferroni post hoc test to compare the markers and histopathological changes in different groups. The GraphPad Prism version 8.1 was used to do the statistical analysis. Results: As indicated by a statistically significant increase (P<0.0001) in TNFα and ICAM-1 level, doxorubicin-induced cardiotoxicity. Additionally, the level of GSH, SOD, and caspase-3 did not differ significantly between the DOX+CoQ10 group and the control group. Furthermore, lesions and histological alterations were induced by the substance. Significant reductions in cardiotoxicity were observed with the administration of coenzyme Q10, as indicated by notable increases (P<0.0001) in SOD, GSH, and TNFα and significant decreases (P<0.0001) in caspase 3 when compared to the DOX group. Also, the CMYO score and lesions exhibited a substantial improvement. Conclusion: In this investigation, coenzyme Q10 exhibited cardioprotective effects against DOX-induced damage to the mouse heart. This phenomenon potentially pertains to inhibiting and safeguarding against oxidative stress, the pathway of apoptosis, and the inflammatory response.